Avaliação do sistema de irrigação por sulco da fazenda do alto em campos dos Goytacazes-RJ - Oliveira, Vicente de Paulo Santos de; Bernardo, Salassier (IRRIGA, 1997)
Avaliação do sistema de irrigação por sulco da fazenda do alto em campos dos Goytacazes-RJ